A Technique to Perform PCI and Stenting in an Anomalous RCA from the Left Sinus of Valsalva - Dazhong Sun; Douglas Bogart (Case Reports in Cardiology)
This describes a technique for the successful performance of percutaneous coronary intervention in patients whose right coronary artery arises from the left sinus of Valsalva and in whom the standard guiding catheters do not allow coaxial support.